Effects Of Andrographis Paniculata, Carica Papaya And Cassia Alata Extracts On The Reproductive Systems Of Mice - Abdullah, Azmahani (2003)
In facing the high rise of population especially in developing countries, a continuing need is felt for oral and non-surgical methods of contraception. Plants extracts have been used widely in traditional medical practice especially as an anti-fertility agent. The Andrographis paniculata, Cassia alata and Carica papaya extracts have been reported to poses multifunctional properties. In the present studies, the effects of 20 mg/kg body weight ethanol extract of Andrographis paniculata, Carica papaya and Cassia alata on the reproductive systems was studied after 30 days and 90 days of treatment in female and male mice. Clomiphene citrate, given daily at 50 mglkg body weight, was used for the purposed comparison. Results obtained showed that the female genital organs (ovaries and uteri) weight was reduced significantly after treatment with Carica papaya and Andrographis paniculata respectiVely. All females groups showed changes in fertility and reduction in litter number.